2008
DOI: 10.1136/bmj.39514.554375.ae
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and injecting drug use

Abstract: Injecting drug use has adverse effects on pregnancy and perinatal outcomes. Methadone treatment improves birth rate but carries a risk of neonatal abstinence syndrome; withdrawal of methadone during pregnancy is not recommended

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…6 Recent studies in women with uncomplicated pregnancies have demonstrated the safety of gradual detoxification with methadone or clonidine in highly monitored inpatient settings. 26, 27 Although no standard protocols exist for opioid detoxification during pregnancy, the Center for Substance Abuse Treatment (CSAT), of the Substance Abuse and Mental Health Services Administration (SAMHSA), recommends methadone tapers of 1.0 to 2.5 mg per day for inpatients and by 2.5 to 10.0 mg per week for outpatients.…”
Section: Management Of Detoxificationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Recent studies in women with uncomplicated pregnancies have demonstrated the safety of gradual detoxification with methadone or clonidine in highly monitored inpatient settings. 26, 27 Although no standard protocols exist for opioid detoxification during pregnancy, the Center for Substance Abuse Treatment (CSAT), of the Substance Abuse and Mental Health Services Administration (SAMHSA), recommends methadone tapers of 1.0 to 2.5 mg per day for inpatients and by 2.5 to 10.0 mg per week for outpatients.…”
Section: Management Of Detoxificationmentioning
confidence: 99%
“…Despite these obstacles, pregnant women can be highly motivated to reduce substance use and most women strive for healthier pregnancy, providing a unique window of opportunity for intervention in this population. 6 Prior studies suggest that pregnant women struggling with addiction not only attempt to reduce their substance use, they also seek improved nutrition, sleep, and other life-style changes. 7 …”
Section: Introductionmentioning
confidence: 99%
“…A recent review article suggests that maternal methadone use is not associated with adverse postnatal development 21. However, there are numerous data linking maternal opiate misuse with developmental delay at ages ranging from 6 months to 12 years 22 23 24 25 26 27 28 29 30 31 32.…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…In theory, maintenance improves psychosocial circumstances for mothers and increases medical compliance among pregnant patients [1]; but, in fact, many at-risk women abuse medical opioids during pregnancy [2]. Substitution therapy frequently leads to the newborn suffering through neonatal abstinence syndrome [3]. In developing rats, myelination is altered by perinatal exposure to therapeutic doses of methadone [4].…”
Section: Introductionmentioning
confidence: 99%